The Rise of the Democracy - Clayton, Joseph, 1868-1943 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Rise of the Democracy" by Joseph Clayton is a historical account written in the early 20th century. The work explores the evolution of political democracy in England, tracing its development from early struggles against monarchical absolutism through significant events such as the signing of the Magna Carta and the establishment of parliamentary representation. The book seeks to illuminate the persistent fight for self-governance by the English people, highlighting key figures and movements that have shaped democratic ideals. The opening of the work sets the stage for an in-depth examination of England's march toward democracy. It begins with a focus on the British influence on global democratic movements, detailing how the notion of governance by elected representatives emerged from centuries of resistance against tyranny and autocracy. Clayton emphasizes the importance of historical landmarks, such as the roles played by church leaders like Anselm and Thomas à Becket, which laid the groundwork for constitutional liberties. As he outlines the key themes of the book, he points out that while democracy in England evolved through practical reforms and not through grand political philosophies, it nonetheless represents a significant development in the struggle for individual liberties and collective governance. (This is an automatically generated summary.)
Release date is 2006-10-23
E-text prepared by Afra Ullah, Keith Edkins, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Democracy; Great Britain -- Politics and government